Analysis of COVID-19 Collective Irrationalities Based on Epidemic Psychology - Luo, Hua; Ren, Yu (Frontiers in Psychology, 2022)
As the SARS-CoV-2 virus swept the world in late 2019, it has brought widespread fear, some suspicion, and degrees of stigma. In the shadow of the COVID-19 pandemics, a series of collective irrationalities such as panic buying, protest marches against vaccines, and pandemic stigma occurred. This phenomenon is inseparable from the spread of rumors about the epidemic. The advent of social media has radically changed the way we consume information and form opinions and made a flood of digital misinformation becoming ubiquitous. The diffusion of false rumors affects the public’s perception of reality and disrupts the prevention of the epidemic. This paper analyzes the COVID-19 collective irrationalities from epidemic psychology to provide a new reference view for overcoming psychological problems related to COVID-19.